Portable blood flow velocimetry for health care monitoring - Noor Azmi, Azran Azhim; Yohsuke, Kinouchi (LAP LAMBERT Academic Publishing, 2014)
The purpose of this book is to provide a detailed explanation on the construction of a portable Doppler ultrasound system for medical application. It is hoped that researchers and the general public will benefit from reading this book to help them to better understand the basics and application of Doppler ultrasound system especially in the clinical setting. Included are data from several experiments involving the portable Doppler ultrasound system to analyse blood velocity in common carotid arteries in subjects with various medical and physical backgrounds. The focus is mainly on blood velocities in common carotid artery and how the information could be used to evaluate the risk of cardiovascular disease in hypertensive patients. The experiments include the association of regular exercise in improving blood velocities to manage the risk of hypertension and cardiovascular disease.